Аnalysis of cointegration relationships between Аzerbaijan’s balance of payments and world oil prices - N. S. Ayyubova (Финансы: теория и практика, 2025)
In a number of countries, an important economic problem is the imbalance of foreign economic relations, which manifests itself, in particular, in the positive and negative balances of the current account of the balance of payments. The purpose of the study is to investigate the impact of rising oil prices on Azerbaijan’s balance of payments using a vector error correction model (VECM). In the paper, the analysis correctly applied econometric methods, the necessary statistical procedures to determine the order of integration of non-stationary time series of Azerbaijan’s current account balance and the prices of Brent crude oil and West Texas Intermediate, covering the period from 1995 to 2024, to identify and evaluation of the model parameters to check the adequacy and validity of the forecast values both in the short term and in a long term. When constructing survey graphs and implementing econometric test procedures, the Eviews and Excel application packages were used. As a result of this study, a VECM was formulated, which makes it possible to carry out an economic and statistical analysis of the functioning of the current account of the balance of payments and world oil prices. The constructed models make it possible to measure both deviations from the equilibrium state and the rate of equilibrium recovery. It is concluded that the long-term equilibrium relationship between the variables can be considered stable, as stability is restored in short periods after disturbances from shock reactions to changes in world oil prices. The constructed models make it possible to measure both deviations from the equilibrium state and the rate of equilibrium restoration.